Resource usage efficiency in sheep breeding enterprises in Konya province and effects of different production strategies on profitability - GUNLU, A; CETIN, O; KIRIKCI, K; TEPELI, C (The Indian Journal of Animal Sciences, 2014)
General characteristics of sheep breeding in Konya region of Turkey, and resource usage efficiency level were determinedby using Cobb-Douglas type production function. Geometric means of 1998/99 and 1999/00, which were surveyedfrom 51 enterprises that were determined by using randomly layer sampling method, were used. The percentage sheepbreeding enterprises income was determined as lamb sales, milk sales, inventory value increases, wool sales and manurerevenues, which were 70.09%, 23.49%,4.28%, 1.53% and 0.77% respectively. Sheep breeding enterprises expendituredistribution were found on feed, labour, veterinary services, depreciation cost and other expenditure, and the values were53.03 %, 31.33 %, 3.41 %, 7.91 % and 4.33 % respectively. Financial ratio and rantability factor were estimated to be18.55 and 25.76 respectively. The marginal value productivity of input factors at feed, labour, veterinary services, depreciation cost and other expenditure were 1.78 TL, 1.74 TL, -9.25 TL, 5.88 TL and -2.80 TL respectively. Return toscale in sheep breeding enterprises in Konya was 0.91 .